2019
DOI: 10.3390/ijerph16122156
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior: A Key Component in the Interaction between an Integrated Lifestyle Approach and Cardiac Autonomic Function in Active Young Men

Abstract: This study aimed to verify the association between autonomic cardiac function (CAF) and the integration of caloric expenditure by physical activity (PA) intensity, sedentary behavior (SB), and sleep quality (PSQI) in active young men. Thirty-five subjects were included, and caloric expenditure in moderate-to-vigorous and light-intensity PA, SB, and PSQI were assessed using questionnaires. Heart rate variability (HRV) was recorded for short periods of time in the supine and orthostatic positions. Multiple linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Thus, we built a method to assess nutritional status in adolescents by estimating body fat percentage using low cost and easy application parameters. The method used for estimation was the MLR, which was already successfully applied to solve several problems such as clinical data analysis [47] to verify the association between autonomic cardiac function and clinical variables [49]; to investigate the effects of food contamination on gastrointestinal tract morbidity [50]; and soil density measurement [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we built a method to assess nutritional status in adolescents by estimating body fat percentage using low cost and easy application parameters. The method used for estimation was the MLR, which was already successfully applied to solve several problems such as clinical data analysis [47] to verify the association between autonomic cardiac function and clinical variables [49]; to investigate the effects of food contamination on gastrointestinal tract morbidity [50]; and soil density measurement [48].…”
Section: Discussionmentioning
confidence: 99%
“…In many areas of knowledge, such as engineering and health, many problems involve investigating the relationship between two or more variables [47,48,49,50]. Multiple linear regression (MLR) is a statistical technique widely used in the literature to verify the relationship between a dependent variable and several independent variables [51].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, higher resting HR and lower HRV have been proposed as an important linking mechanism between ST and CVD [18][19][20]. However, observational studies evaluating the association between ST and HR or HRV in adults have reported inconsistent results including negative, positive, and null associations [18,[20][21][22][23][24][25][26]. To address this uncertainty, we systematically reviewed the current evidence relating ST to HR and HRV to shed light on whether this proposed mechanism is supported by the available research and to clarify the potential role of cardiac-autonomic dysfunction in the association of ST with CVD and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Some variables demonstrated by research to be the most influential in a healthy lifestyle are eating habits, physical activity, physical inactivity, and emotions [ 11 ]. A healthy lifestyle is a key component in fostering healthy aging and in reducing the risk of cardiovascular events, which requires, among other aspects, participating in regular physical activity, reducing sedentary behavior, and maintaining a good quality of life [ 12 ]. Some studies [ 13 , 14 , 15 ] have connected the impact of physical activity and physical inactivity with quality of life.…”
Section: Introductionmentioning
confidence: 99%